INTERNALISASI NILAI-NILAI PERAYAAN SHALAWATAN DALAM MEMBANGUN KARAKTER RELIGIUS - Fauzi, Ahmad (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2019)
Research on the celebration of prayer in the social and cultural community of Probolinggo, in essence, is inseparable from the value of local wisdom, as part of religious rituals in expressing its religion, with the aim to invoke blessings and safety both individually and socially. This research specifically focuses on the meaning of the celebration of shalawatan and the construction of symbolization of shalawatan values. In this context, to answer the problem above, the researcher uses the theory of symbolic interactionism, through dialectical intermediate (mind, self, society). Therefore, the interpretation of the meaning of the celebration of shalawatan, giving birth to various social symbols, then interpreted as part of the process of the formation of individual social behavior for the better. At the level of praxis, internalization the values of shalawatan celebrations significantly gives birth to several aspects; shalawatan as part of the formation of the character (good character); social harmonization; moral bull and the giving of souls (tazkiyyat al-nafs).